PENGUKURAN KINERJA KEUANGAN BERBASIS MAQASHID SYARIAH INDEX - Widia Lestari, Elsa; Inez Fitria, Inez; Miftahul Jannah; Meryana, Shinta; Sundari, Asri (Pelita Nusa Jurnal, published by the Institute for Research and Community Service (LP2M) of the Pelita Nusa Islamic Religious College West Bandung (STAI PENUS), 2025)
This study aims to measure the performance of Islamic banks using the Maqashid Syariah Index (MSI) approach, which focuses on three main objectives, namely tahzib al-fard (individual education), iqamah al-'adl (enforcement of justice), and jalb al-maslahah (maintenance of benefits). This approach is different from conventional methods such as CAMELS and EVA ratios which focus more on financial aspects. The research uses a qualitative method with a descriptive approach based on library research. The results of the study show that the implementation of MSI provides a more comprehensive picture of the performance of Islamic banks because it is able to assess financial aspects as well as social functions according to sharia principles. These findings confirm the importance of using MSI as an alternative to measuring the performance of Islamic banking to be in line with the goals of maqashid sharia.